BUSE OF INNOVATIVE TECHNOLOGIES IN STUDYING CHARACTERISTICS OF CHANGE OF SPEECH SOUNDS IN ELEMENTARY CLASSES - Hakimova Dilovar Gayratovna (American Journals, 2023)
This article is about changing of speech sounds with innovation technologu.
Keywords: Lingvistic, fonetk, grammatic, verb, uzbek language, innovatsion.